2021
DOI: 10.1080/19942060.2021.1966837
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of daily water level using new hybridized GS-GMDH and ANFIS-FCM models

Abstract: Accurate prediction of water level (WL) is essential for the optimal management of different water resource projects. The development of a reliable model for WL prediction remains a challenging task in water resources management. In this study, novel hybrid models, namely, Generalized Structure-Group Method of Data Handling (GS-GMDH) and Adaptive Neuro-Fuzzy Inference System with Fuzzy C-Means (ANFIS-FCM) were proposed to predict the daily WL at Telom and Bertam stations located in Cameron Highlands of Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 84 publications
0
15
0
Order By: Relevance
“…The authors argued that they found the DL slightly superior to the FFNN in only over one-half of the lakes, and its performances did not significantly surpass those of the FFNN model in terms of R and RMSE values. Ebtehaj et al (2021) reported better performance of hybrid models (GS-GMDH: RMSE = 82.98 and ANFIS-FCM: RMSE = 83.8) compared to standalone models (GMDH: RMSE = 88.05 and GEP: RMSE = 88.22) for predicting water level at two stations in Malaysia.…”
Section: Introductionmentioning
confidence: 94%
“…The authors argued that they found the DL slightly superior to the FFNN in only over one-half of the lakes, and its performances did not significantly surpass those of the FFNN model in terms of R and RMSE values. Ebtehaj et al (2021) reported better performance of hybrid models (GS-GMDH: RMSE = 82.98 and ANFIS-FCM: RMSE = 83.8) compared to standalone models (GMDH: RMSE = 88.05 and GEP: RMSE = 88.22) for predicting water level at two stations in Malaysia.…”
Section: Introductionmentioning
confidence: 94%
“…Some of the most popular and widely used FIS generation methods are fuzzy C-means clustering (FCM), sub-clustering (SC) and grid partitioning (GP). Recent studies (Safari et al 2019;Ebtehaj et al 2019a;2021) have shown that not only the accuracy of FCM modeling is better than the other two methods, but it also has a higher modeling speed. Moreover, the parameters that must be optimized during the training process in this method are less than the other two methods.…”
Section: And a N Is K Nzmentioning
confidence: 99%
“…However, the major drawback of NF is that its performance significantly is susceptible to the selection and optimization of the input variable's fuzzy membership function. The state-of-the-art hybrid AI model displayed promising prediction results over standalone models in different hydrological studies (Maroufpoor et al, 2019a;Pham et al, 2019;Maroufpoor et al, 2020;Mohammadi et al, 2020;Ebtehaj et al, 2021;Malik et al, 2021;Sammen et al, 2021). Therefore, such models may be a suitable alternative to standalone models in DO prediction.…”
Section: Introductionmentioning
confidence: 99%